Influence of Physical Conditions at Home, Mother's Cooking Habits with ISPA Incidence in Toddlers in Dulolong Village - Koli, Sukmawati; Adu, Apris; Ndoen, Honey Ivon (Timorese Journal of Public Health, 2023)
ARI is a respiratory tract infection characterized by a fever of 38°C and accompanied by one of the symptoms/signs of respiratory disease such as cough/shortness of breath/sore throat/cold/mild to severe pneumonia (Kemenkes RI, 2020). Home and environmental conditions that do not meet health requirements can be a place for the transmission of environmental-based diseases such as Acute Respiratory Infections (ARI). Dulong Village is one of the villages in the working area of ​​the Alor Kecil Health Center which experienced an increase in the number of ARI cases, from 97 cases in 2018 to 119 cases until October 2020 (Puskesmas Alor Kecil, 2020). This study aims to determine the relationship between the physical condition of the house, the mother's cooking habits with the incidence of ARI in children under five in Dulolong Village. This study uses an analytical survey with a case-control design. The population in this study were all children aged 1-5 years in Dulolong Village, as many as 124 children under five consisting of 69 children under five for the case population and 55 under five for the control population. The sampling technique using the case-control formula obtained 35 samples with a ratio of 1: 1 so that a sample of 70 children under five was needed according to the predetermined inclusion and exclusion criteria. Collecting data using questionnaires, observations, interviews, and documentation. After the data was collected then the data was processed and analyzed using the Chi-square test. From the results of the study, it was found that there was a relationship between ventilation area (p = 0.017; OR = 3.69), type of floor (p = 0.004; OR = 5.06), occupancy density (p = 0.004; OR = 4.79), ownership of holes smoke (p = 0.028; OR = 3.43), maternal habits (p = 0.002; OR = 5.45) with the incidence of ARI in children under five in Dulolong Village. Toddlers who live in houses with wooden/woven walls are 1.18 times more likely to get ARI compared to toddlers who live in houses with brick walls/plaster walls (p = 1,000).